2012
DOI: 10.1103/physrevb.85.214405
|View full text |Cite
|
Sign up to set email alerts
|

First-principles study of spin-disorder resistivity of heavy rare-earth metals: Gd–Tm series

Abstract: Electrical resistivity of heavy rare-earth metals has a dominant contribution from thermal spin disorder scattering. Here this spin-disorder resistivity is calculated for the Gd-Tm series of metals in the paramagnetic state. Calculations are performed within the tight-binding linear muffin-tin orbital method using two complementary methods: (1) averaging of the Landauer-Büttiker conductance of a supercell over random noncollinear spin-disorder configurations, and (2) linear response calculations with the spin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Theoretical studies have shown that the resistivity (ρ) in normal metals and alloys contains two dominant mechanisms, namely, the scattering of conduction electrons on impurities and other structural defects. [ 43–45 ] In our work, the gradual increase in the Pt 1‐x Gd x alloy compositions can be viewed as strong interface modification. With a much larger atomic radius of Gd (0.97 Å) than that of the Pt (0.63 Å), the replacement of Gd to Pt will result in an increase in lattice constant, which will modify the interface morphology.…”
Section: Resultsmentioning
confidence: 87%
“…Theoretical studies have shown that the resistivity (ρ) in normal metals and alloys contains two dominant mechanisms, namely, the scattering of conduction electrons on impurities and other structural defects. [ 43–45 ] In our work, the gradual increase in the Pt 1‐x Gd x alloy compositions can be viewed as strong interface modification. With a much larger atomic radius of Gd (0.97 Å) than that of the Pt (0.63 Å), the replacement of Gd to Pt will result in an increase in lattice constant, which will modify the interface morphology.…”
Section: Resultsmentioning
confidence: 87%
“…probability between the two leads is calculated for pairs of atoms in atomic layers which are chosen at a distance enough far away from the interface with the scattering region as to ensure their bulk-like potentials [222]. The disorder effect in diverse material properties was previously modeled employing the supercell approach, e.g., the spin-disorder resistivity [215,217,218,219], or the frozen thermal lattice disorder effect on the Gilbert damping and the spin-flip diffusion length [223,224]. The disordered local moment method in the coherent potential approximation, begin computationally cheap, can be also used to evaluate the spin disorder effect but a complete disorder saturation above the critical temperature due to the missing short range order can lead to significant differences in the results [216].…”
Section: Electron Transport With Real Space Spin Disordermentioning
confidence: 99%
“…We estimate the spin disorder contribution to the resistivity from the slope of the resistance as a function of the TL thickness (leadto-lead distance) at T = 500 K with almost fully saturated spin disorder. Assuming that the Ohmic limit is fulfilled for the thickness of 9 Cr layers [217,218], the spin disorder contribution to the resistivity…”
Section: Crte Nanostructures Between Ag Leadsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, the alloy analogy has been exploited extensively in the past when dealing with the impact of spin fluctuations on various response quantities. The representation of a frozen spin configuration by means of supercell calculations has been applied for calculations of the Gilbert parameter for α [18] as well as for the resistivity or conductivity [18,22,23]. Also, the CPA has been used for calculations of α [24] as well as the resistivity [21,25].…”
Section: Introductionmentioning
confidence: 99%